Global-scale quantification of mesopelagic fish-mediated carbon fluxes - Qingxia Liu; Zuozhi Chen; Li Zhang; Grace K. Saba; Linbin Zhou; Honghui Huang (Marine Environmental Research, 2026)

Magnolol disrupts membrane integrity and enhances colistin activity via a NagR-Mediated susceptibility in foodborne Aeromonas hydrophila - Xin Chen; Jinpeng Shi; Siyan Chen; Linbin Chen; Shuaiyuan Tang; Ruixiang Shi; Zhihan Yu; Wenbo Yu; Tianlong Lai; Yibin Liao; Liping Li; Xiangmin Lin (Food Bioscience, 2026)

A knowledge graph approach to global nickel mining operations: Patterns and geopolitical insights - Zipeng Lin; Peng Wang; Linbin Tang; Francesca Larosa; Yongguang Zhu; Paul Ekins; Wei-Qiang Chen (Sustainable Production and Consumption, 2025)

Iron as a Modifiable Factor for Adverse Pregnancy Outcomes: Refining and Understanding Causal Estimates Using Mendelian Randomization - Yuhang Wu; Linbin He; Chu Liu; Fan Xia; Ziye Li; Lizhang Chen; Tingting Wang (Biological Trace Element Research, 2025)

Electronic effect in bromide-modified noble metal catalysts promotes highly stable and selective hydrogenation - Xintai Chen; Mengqi Yang; Qiying Liu; Xiaoling Mou; Linbin Ying; Yu Meng; Ronghe Lin; Yunjie Ding (Chemical Engineering Journal, 2024)

Comparison of Adaptive Simulation Observation Experiments of the Heavy Rainfall in South China and Sichuan Basin - Linbin He; Weiyi Peng; Yu Zhang; Shiguang Miao; Siqi Chen; Jiajing Li; Duanzhou Shao; Xutao Zhang (Advances in Atmospheric Sciences, 2024)

Orbital interactions and high spin states: Unlocking the potential of Co-Single-Atom catalysts for Li-S batteries - Wei Yan; Jun Chen; Tongde Wang; Abdul Mateen; Linbin Tang; Shiqiang Sun; Chenxi Jin; Jiawen Li; Haojie Li; Jing Chen; Guohua Gao; Guangming Wu; et al. (Chemical Engineering Journal, 2024)

Evaluating the bulk commodities supply risk from the perspective of physical trade - Jianlimin Wei; Wei-Qiang Chen; Chuke Chen; Yuanyi Huang; Linbin Tang (Resources Policy, 2024)

Cellulose nanofibers embedded chitosan/tannin hydrogel with high antibacterial activity and hemostatic ability for drug-resistant bacterial infected wound healing - Dangwei Li; Xiangyang Dong; Xia Liu; Heng Lin; Di Yang; Xiaowen Shi; Chaoji Chen; Fenghua Tao; Linbin Jiang; Hongbing Deng (Carbohydrate Polymers, 2024)

Introduction of isotopically light barium from the Rainbow hydrothermal system into the deep Atlantic Ocean - Zhouling Zhang; Linbin Zhou; Xue-Gang Chen; Eric P. Achterberg; Yang Yu; Ed Hathorne; Zvi Steiner; Christopher Siebert; Martin Frank (Earth and Planetary Science Letters, 2024)

High burdens of phosphorylated tau protein and distinct precuneus atrophy in sporadic early-onset Alzheimer’s disease - Xinyi Lv; Zhaozhao Cheng; Qiong Wang; Feng Gao; Linbin Dai; Chen Du; Chang Liu; Qiang Xie; Yong Shen; Jiong Shi (Science Bulletin, 2023)

Exploring the global trade networks of the tungsten supply chain: Insights into the physical and monetary mismatch among countries - Linbin Tang; Peng Wang; Zijie Ma; Stefan Pauliuk; Wei‐Qiang Chen; Tao Dai; Zipeng Lin (Journal of Industrial Ecology, 2023)
International trade is essential to bridge the imbalance between supply and demand of materials along with different nations effectively, especially for critical raw materials such as tungsten that are highly geographically unequally distributed. However, the international trade flows and their complex networks that link those participating nations have remained largely unexplored, which leads to inexplicable concerns for materials' criticality and their supply risks. By integrating the material flow analysis and the complex network analysis, this study traces the global trade flows of tungsten in various forms ranging from primary products to scrap among 223 countries and regions annually from 2000 to 2018 and explores the evolution of participating countries' role involved in international trade networks from both physical and monetary perspectives. We found that (1) there are ∼2673 thousand metric tons of tungsten feeding into supply chains globally during the 19 years, and about 96% of tungsten resources are re‐allocated from Asia to the high‐income regions; (2) the high‐income countries gain the potential benefits from both the resources and economic perspectives and they import 72% of tungsten resources in the form of primary and semi‐products from developing countries, meanwhile earning 87% of global tungsten trade value by exporting tungsten metal products with high value‐added back to those tungsten resources suppliers. Under the growing national interconnections of global tungsten trade networks, this study urges more cooperative actions and targeted supply chain management among the participating countries to secure the tungsten supply and sustainability of the global tungsten cycle.

Mapping China's copper cycle from 1950–2015: Role of international trade and secondary resources - Min Hao; Linbin Tang; Peng Wang; Heming Wang; Qiao-Chu Wang; Tao Dai; Wei-Qiang Chen (Resources, Conservation and Recycling, 2023)

Important photosynthetic contribution of silique wall to seed yield-related traits in Arabidopsis thaliana - Xiaoyi Zhu; Liang Zhang; Chen Kuang; Yan Guo; Chunqian Huang; Linbin Deng; Xingchao Sun; Gaomiao Zhan; Zhiyong Hu; Hanzhong Wang; Wei Hua (Photosynthesis Research, 2018)